2018
DOI: 10.1186/s13640-018-0264-z
|View full text |Cite
|
Sign up to set email alerts
|

Improved BM3D image denoising using SSIM-optimized Wiener filter

Abstract: Image denoising is considered a salient pre-processing step in sophisticated imaging applications. Over the decades, numerous studies have been conducted in denoising. Recently proposed Block matching and 3D (BM3D) filtering added a new dimension to the study of denoising. BM3D is the current state-of-the-art of denoising and is capable of achieving better denoising as compared to any other existing method. However, there is room to improve BM3D to achieve high-quality denoising. In this study, to improve BM3D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(24 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…The PSRN values of MP-CNN model are all larger than WNNM, EPLL, TNRD, DnCNN-S and SCNN models, indicating that MP-CNN had the best effect on noise removal in images. In a study showed that SIMM value was used to improve the filter and found that noise in the image could be removed better [8]. Some researchers used PSNR, MSE and SSIM to carry out a qualitative and quantitative comparison of image indicators [9].…”
Section: Discussionmentioning
confidence: 99%
“…The PSRN values of MP-CNN model are all larger than WNNM, EPLL, TNRD, DnCNN-S and SCNN models, indicating that MP-CNN had the best effect on noise removal in images. In a study showed that SIMM value was used to improve the filter and found that noise in the image could be removed better [8]. Some researchers used PSNR, MSE and SSIM to carry out a qualitative and quantitative comparison of image indicators [9].…”
Section: Discussionmentioning
confidence: 99%
“… Removing the noise Noise reduction is an essential step in image processing due to its importance in obtaining better results, the block matching with three-dimensional filtering (BM3D) denoising is used in this step. Many studies shown that the BM3D filter is very important in term of noise reduction due to its results comparing with other filters [9,10]. The implementation of this filter is explained in detail in [11]  Contrast…”
Section: Telkomnika Telecommun Comput El Controlmentioning
confidence: 99%
“…After the development of the best analytical solution, BM3D [8], [18], little improvement in denoising performance was achieved until the advent of deep learning denoisers [59]. Recent Convolutional Neural Network (CNN) based methods achieve state-of-the-art image denoising performance and are even faster than traditional optimizationbased approaches [55].…”
Section: Introductionmentioning
confidence: 99%